Pengaruh Kualitas Konten Youtube Channel Nadia Omara Terhadap Kepuasan Penonton pada Mahasiswa Universitas Muhammadiyah Kotabumi - Febrianti Febrianti; Nanda Fitri Latifah; Kamelika Nihayati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Abstract. The development of digital media, especially YouTube, has made this platform not only a means of entertainment, but also a source of information, education, and self-reflection for students. Viewer satisfaction in consuming YouTube content is influenced by the quality of content presented by creators. This study aims to evaluate the impact of the quality of Nadia Omara's YouTube channel content on viewer satisfaction among students at Muhammadiyah University Kotabumi. This study applies a quantitative approach through a survey method. Data were collected through a closed questionnaire with a Likert scale distributed to 98 respondents selected using purposive sampling. The independent variable in this study is content quality, while the dependent variable is viewer satisfaction. Data analysis was conducted through validity testing, reliability testing, linearity testing, and simple linear regression analysis. Hypothesis testing was performed using the t-test (partial test) with the help of SPSS version 26 software. The results showed that the quality of Nadia Omara's YouTube channel content had a positive and significant effect on viewer satisfaction. This is evidenced by a regression coefficient value of 0.865 and a t-value of 11.937 with a significance level of 0.000 (< 0.05). These findings support the Uses and Gratifications Theory and Expectation Confirmation Theory, which emphasize the active role of the audience in evaluating media based on the fulfillment of needs and conformity with expectations empirically among college students.